The Effect of Use of Red Dragon Skin (Hylocereus polyrhizus) Fermented in The Break of External Offal Broiler - N. L. A., Suartiniyanti; Dewi, G. A. M. K.; Dewantari, M. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to determine the effect of using fermented red dragon fruit skin (Hylocereus polyrhizus) in the ration against external offal broilers. The study was conducted at the Teaching Farm of the Faculty of Animal Husbandry, Udayana University, Jimbaran, Badung, Bali which lasted for 5 weeks. The broiler used is 90 tails. The research design used was a completely randomized design (CRD) consisting of 3 treatments and 6 replications. Each replication consists of 5 chickens. The three treatments are RKBN0: red dragon fruit skin ration as a control, RKBN1: ration with 5% fermented dragon fruit peel, and RKBN2: ration with 7% fermented dragon fruit peel. The variables observed in this study were head, neck, foot, and feather weight. The results showed that the treatment of RKBN0, RKBN1, and RKBN2 were not significantly different (P> 0.05) on the weight of head, neck, legs, and broiler hair aged 5 weeks. Based on the results of this study it can be concluded that the administration of 5% and 7% ration of red dragon fruit skin (Hylocereus polyrhizus) does not affect the weight of the head, neck, legs, and broiler feathers 5 weeks aged.   Keywords: dragon fruit skin, fermentation, ration, external offal, broiler